2014
DOI: 10.3382/ps.2014-04210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of eggshell temperature throughout incubation on broiler hatchling leg bone development

Abstract: Leg problems in broiler chickens may partly be prevented by providing optimal circumstances for skeletal development during incubation. One of the factors demonstrated to affect bone development is eggshell temperature (EST), which provides a reliable reflection of embryo temperature. The present experiment aimed to investigate the effect of EST on development and asymmetry of the femur, tibia, and metatarsus in broiler chicken hatchlings. Eggs were incubated from d 0 until hatch at 1 of 4 EST: low (36.9°C), n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 19 publications
1
27
0
2
Order By: Relevance
“…Os resultados obtidos neste estudo estão de acordo com os observados por Van der Pol et al (2) , que verificaram que, em temperatura constante de incubação, houve aumento do peso da bursa de Fabricius em pintos oriundos de matrizes mais velhas, embora os autores não tenham avaliado área de folículo da bursa. Esses resultados também corroboram os observados por Leandro et al (9) que, em estudo com pintos originados de matrizes com diferentes idades, mas em condições ideais de Histomorfometria de órgãos linfoides e desenvolvimento intestinal... temperatura, observaram que matrizes mais velhas originaram pintos com melhor resposta imune.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Os resultados obtidos neste estudo estão de acordo com os observados por Van der Pol et al (2) , que verificaram que, em temperatura constante de incubação, houve aumento do peso da bursa de Fabricius em pintos oriundos de matrizes mais velhas, embora os autores não tenham avaliado área de folículo da bursa. Esses resultados também corroboram os observados por Leandro et al (9) que, em estudo com pintos originados de matrizes com diferentes idades, mas em condições ideais de Histomorfometria de órgãos linfoides e desenvolvimento intestinal... temperatura, observaram que matrizes mais velhas originaram pintos com melhor resposta imune.…”
Section: Resultsunclassified
“…Alguns pesquisadores avaliaram indiretamente a resposta imune das aves por meio de morfometria de órgãos linfoides. Van der Pol et al (2) estudaram o peso do baço e da bursa de Fabricius de pintos neonatos de matrizes com diferentes idades e observaram que pintos oriundos de matrizes mais velhas apresentaram maior peso de bursa de Fabricius.…”
Section: Introductionunclassified
“…(2009) found comparable results at slaughter age when applying a high eggshell temperature ( EST , 38.9°C) during the last 4 D of incubation compared with an EST of 36.9°C. Van der Pol et al. (2014) observed that a high EST (38.6°C) throughout incubation appears to result in lower tibia, femur, and metatarsus lengths at hatch compared with an EST of 36.9°C and 37.8°C.…”
Section: Introductionmentioning
confidence: 92%
“…A lower or higher temperature than this optimum might influence the quality of hatchlings ( Wilson, 1991 , French, 1997 , Tona et al., 2005 ) and embryonic bone development as well. Bone development and growth plate differentiation begins during incubation and incubation temperature has been demonstrated to affect bone development and later life leg health of broiler chickens ( Hammond et al., 2007 , Oviedo-Rondón et al., 2008a , Oviedo-Rondón et al., 2008b , Oviedo-Rondón et al., 2009 , Shim and Pesti, 2011 , Van der Pol et al., 2014 ). Effects of incubation temperature on embryonic bone development and later life leg health might be related to the speed of bone mineralization during incubation.…”
Section: Introductionmentioning
confidence: 99%
“…Leg problems may occur in the pre and post hatch period. Incubation conditions have a significant effect on bone characteristics and leg problems of poultry (Groves & Murin, 2014;Oviedo-Randon et al, 2009;Van der Pol et al, 2014). Bone mineralization and development begin during embryo development, so it is possible for skeletal disorders to develop when the embryo is developing in the egg (Torres & Korver, 2018).…”
Section: Introductionmentioning
confidence: 99%